Source Code Metrics: A Study on Scientific Publications in Brazilian Symposia and the Perception of Computing Students - Monteiro, Cheila Marques; Silva, Conceição Neves; Amorim, Rainer Xavier de; Passos, Odette Mestrinho (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2024)
Context: Software quality is not just about what users see. Code is a key part of software evaluation and improvement, so it is essential to use source code metrics. Problem: There are studies related to the use of source code metrics, but difficulties persist in their practical adoption in real projects. Solution: This study presents the most cited source code metrics in the literature, as well as the perception of computer students on this concept. Is Theory: Organizational Learning Theory. Method: A systematic mapping was conducted to identify the most cited source code metrics. In addition, a survey was conducted with college students in the field of Computer. Summary of Results: As a result of the Mapping, 12 classifications and 67 types of source code metrics were obtained that can help the team in the development of the software product. In addition, 16 participating students who have already completed 75% or more of the course are familiar with the concept of source code metrics, as evidenced by the results of the Opinion Survey. Contributions and Impact in the IS Area: This research highlights a gap in relation to publications that address in a more practical way the use of source code metrics and in the knowledge of college students in source code metrics in the area of computing and reinforces the need to integrate practical experiences and review academic curricula to better prepare future information systems professionals, aiming at the quality of software systems.